Community-Centered Journalism : Engaging People, Exploring Solutions, and Building Trust - Wenzel, Andrea, 1977- (Book collections on Project MUSE., 2020)
"Contemporary journalism faces a crisis of trust that threatens the institution and may imperil democracy itself. Critics and experts see a renewed commitment to local journalism as one solution. But a lasting restoration of public trust requires a different kind of local journalism than is often imagined, one that engages with and shares power among all sectors of a community. Andrea Wenzel models new practices of community-centered journalism that build trust across boundaries of politics, race, and class, and prioritize solutions while engaging the full range of local stakeholders. Informed by case studies from rural, suburban, and urban settings, Wenzel's blueprint reshapes journalism norms and creates vigorous storytelling networks between all parts of a community. Envisioning a portable, rather than scalable, process, Wenzel proposes a community-centered journalism that, once implemented, will strengthen lines of local communication, reinvigorate civic participation, and forge a trusting partnership between media and the people they cover"--